2021
DOI: 10.3390/ijms22063103
|View full text |Cite
|
Sign up to set email alerts
|

MYB-Mediated Regulation of Anthocyanin Biosynthesis

Abstract: Anthocyanins are natural water-soluble pigments that are important in plants because they endow a variety of colors to vegetative tissues and reproductive plant organs, mainly ranging from red to purple and blue. The colors regulated by anthocyanins give plants different visual effects through different biosynthetic pathways that provide pigmentation for flowers, fruits and seeds to attract pollinators and seed dispersers. The biosynthesis of anthocyanins is genetically determined by structural and regulatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
179
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(185 citation statements)
references
References 188 publications
(339 reference statements)
5
179
0
1
Order By: Relevance
“…Among these functions, MYB proteins have been particularly well studied as regulators of phenylpropanoid metabolism, such as the biosynthesis of proanthocyanidins (PAs), anthocyanins, flavonols, and lignin in plants. For example, MYB proteins can bind to the bHLH transcription factor and WD40 protein to form the MBW complex and activate the biosynthesis of PAs and anthocyanins [ 3 , 4 , 5 , 6 ]. Multiple studies have indicated the critical roles of MYB transcription factors in plant stress responses, especially in abiotic stresses [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among these functions, MYB proteins have been particularly well studied as regulators of phenylpropanoid metabolism, such as the biosynthesis of proanthocyanidins (PAs), anthocyanins, flavonols, and lignin in plants. For example, MYB proteins can bind to the bHLH transcription factor and WD40 protein to form the MBW complex and activate the biosynthesis of PAs and anthocyanins [ 3 , 4 , 5 , 6 ]. Multiple studies have indicated the critical roles of MYB transcription factors in plant stress responses, especially in abiotic stresses [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, all of 15 transcripts associated with JA biosynthesis identified by MapMan analysis were found to respond to HL stress and were up-regulated by HL ( Figure 8 A). Several studies have reported that JA mediates the biosynthesis and accumulation of anthocyanins in plants when they are exposed to adverse environmental conditions [ 40 , 42 , 44 , 45 ]. In our study, RT-qPCR analysis of five JA biosynthesis-associated genes also indicated that the expression of all of them was induced in rapeseed leaves by HL stress, supporting the results of the transcriptome analysis ( Figure 8 B).…”
Section: Resultsmentioning
confidence: 99%
“…R2R3-MYB TFs, a type of the ternary MBW complex, have been reported to play a dominant role in the regulation of anthocyanin biosynthesis [ 40 ]. Notably, MYB75/PAP1 and MYB90/PAP2 genes are induced by light in Arabidopsis [ 84 ], and their orthologs were found to be induced by 7- and 23.5-fold, respectively, in leaves of rapeseed seedlings exposed to HL conditions for 16 h in rapeseed under HL ( Figure 9 C) which is consistent with the observed anthocyanin accumulation under HL conditions in our study ( Figure 1 C,D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R2R3-MYBs such as IbMYB1 can independently initiate the transcription of anthocyanin biosynthesis genes ( Stracke et al, 2007 ; Dubos et al, 2008 ; Dong, 2014 ; Dong et al, 2014 ) or can interact with other TFs to form the MBW complex to activate anthocyanin biosynthesis in sweet potato and other plants ( Dubos et al, 2008 ; Davies et al, 2012 ; Zhu et al, 2015 ; Deng et al, 2020 ; Yan et al, 2021 ). It has been confirmed that IbMYB1-2 plays a vital regulatory role in anthocyanin accumulation in storage roots ( Tanaka et al, 2011 ), but it is not necessary in all varieties for the expression of IbMYB1 ( Kim et al, 2010 ; Li et al, 2019 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%